Cryogenic Tribology of High-Speed Bearings and Shaft Seals in Liquid Hydrogen - Masataka Nosaka (Japanese Society of Tribologists, 2011)
Liquid hydrogen (LH2) is excellent in extensive storage and transportation systems, such as being used as fuel in highly efficient liquid-rocket engines. To consider the use of LH2 required for future hydrogen-energy systems, this paper presents a topical review of previous cryogenic tribology studies on the research and development of the bearings and shaft seals for LH2 turbopumps. Cryogenic tribology studies were conducted for the LE-5/LE-7 rocket engines of the Japanese H-2 rocket as well as for an advanced ultra-high-speed LH2 turbopump. The tribo-chemical formation of CaF2/FeF2 film due to the reduction power of LH2 showed excellent self-lubrication, resulting in a sound wear condition within the turbopump bearing. A new hybrid ceramic bearing with Si3N4 balls, which bearing had a single-guided retainer, tested excellently at an ultra-high speed of 120,000 rpm (3 million DN) in LH2. Seal performance for the floating-ring seals using Ag-plated metal seal-rings at ultra-high speeds was also tested.